(untitled) (Aintelia Science Notes, 2026)
In this study, the surface interactions of cationic surfactant-based conditioning systems on hair fibers and the resulting performance outcomes were comprehensively evaluated. The negatively charged surface characteristics of hair fibers, particularly after washing, facilitate the adsorption of cationic agents onto the hair surface via electrostatic attraction. As a result of this adsorption mechanism, a low-friction film layer is formed on the hair surface, reducing inter-fiber interaction forces and improving combability performance. Within the scope of the study, formulations containing cationic conditioning systems were comparatively evaluated against reference systems, and all formulations were standardized based on an equivalent active matter concentration of 2%. Wet and dry combing performance was assessed using a texture analyzer by measuring combing force values. Sensory evaluations were conducted by trained panelists under a blind test protocol and scored using a multi-parameter approach. The findings demonstrated that cationic systems form a homogeneous and stable film layer on the hair surface, significantly reducing the coefficient of friction and markedly improving both wet and dry combability. Furthermore, a strong correlation was observed between sensory evaluation results and instrumental measurements. In conclusion, cationic surfactant-based conditioning systems provide high-performance and sensorially optimized solutions in modern hair care formulations.